The role of non-state actors in regime formation: Case study on Internet governance. - Elkhishin, Sameh Mohamed (AUC Knowledge Fountain, 2016)
Many scholars argue that the Internet is a symbol of globalization and avoidance of state control. The Internet governance negotiations, which aims to establish an international regime for the Internet, is conducted through a multi-stakeholder setting associated with extensive involvement of non-state actors. This has been viewed as an indicator for a 'diminishing state role' in international relations; particularly, formation of international regimes. This study indicates that the role of states does not diminish in regime formation. States, especially great powers, are the main actors that set international principles, norms, rules and decision-making procedures. They create regimes in order to regulate international behavior as to global sectors, including the Internet. States deliberately enable certain non-state actors to participate in regime formation and governance of some global sectors, based on conscious perception of the utility and usefulness of such participation.